Differential Strain-Specific Responses of Trichoderma spp. in Mycoparasitism, Chitinase Activity, and Volatiles Production Against Moniliophthora spp. - María F. Garcés-Moncayo; Christian A. Romero; Simón Pérez-Martínez; Carlos Noceda; Luís L. Galarza; Daynet Sosa del Castillo (Microorganisms)
Moniliophthora roreri (MR, frosty pod rot) and M. perniciosa (MP, witches’ broom disease) pose critical threats to cacao production in Latin America. This study explores the biocontrol potential of Trichoderma spp. strains against these pathogens through exploratory analysis of mycoparasitism, chitinolytic activity, and volatile organic compound (VOC) production. Dual-culture assays revealed species-specific antagonism, but C2A/C4B showed a dual-pathogen efficacy (>93% of Monioliopthora inhibition). Chitinase activity revealed C4A/C1 strains as exceptional producers (72 mg/mL NAGA vs. MR and 94 mg/mL vs. MP, respectively). GC-MS analysis identified pathogen-modulated VOC dynamics: hexadecanoic acid dominated in 80% Trichoderma solo-cultures (up to 26.65% peak area in C3B). MP showed 18.4-fold higher abundance of hexadecanoic acid than MR (0.23%). In 90% of dual-culture with MR and MP, HDA was detected as the most abundant. Functional specialization was evident. C4A and C1 prioritized chitinase production growing on MR and MP cell walls (respectively), whereas C9 excelled in antifungal hexadecanoic acid synthesis in confrontation with both pathogens. Complementary strengths among strains—enzymatic activity in C4A/C4B versus volatile-mediated inhibition in C9—suggest niche partitioning, supporting a consortium-based approach for robust biocontrol. This study provides preliminary evidence for the biocontrol potential of several Trichoderma strains, showing possible complementary modes of action.